The Issues of the Sixth Dalai Lama and the Transformation of Qing Information System on Tibet - Kung, Ling-Wei (Religions, 2025)
After having been deceived by the Géluk government about the death of the Fifth Dalai Lama for almost 15 years, the Qing empire decided to strengthen its surveillance on Tibet by deploying espionage networks operated by spy lamas based in Xining and Dartsédo on Sino–Tibetan borderlands. Accordingly, the Qing successfully intervened in the reincarnation system of Tibetan Buddhism by taking advantage of the Sixth Dalai Lama’s issues. By establishing a new system of espionage operated by a eunuch lama serving in the imperial court, the Qing finally deposed the Sixth Dalai Lama and secretly murdered him in 1706. The Sixth Dalai Lama’s death embodied the monumental transition that significantly shaped the destiny of Tibet, China, and Inner Asia in the following three centuries. By investigating the Sixth Dalai Lama’s controversies, this article sheds light on how the Qing dynasty embarked on constructing its imperial enterprise in Inner Asia based on intelligence collection and information manipulation. By using multilingual sources in Tibetan, Mongolian, Manchu, and Chinese, the present study shows how the Qing empire overcame the challenges of information deficiency and lingual differences by developing intelligence networks and multilingual mechanisms to consolidate its governance in Inner Asia.